VALORIZATION OF EGGSHELLS WASTE FOR BREAD PRODUCTION - NICOLETA PLATON; ANA-MARIA GEORGESCU; VASILICA-ALISA ARUŞ; IULIANA SION; MIHAELA SILION; ALINA-VIOLETA URSU; ILEANA-DENISA NISTOR (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This paper treats the effect of addition of unconventional materials as eggshell (ES) derived products for improving the quality of bread and bakery products. The main goal of this study is to demonstrate the feasibility of eggshells macerated (ESM) that contains a high assimilable calcium source (i.e. calcium citrate) as a supplement in white bread formulation. The influence of different percentage of ESM (i.e. 2.5 %, 5.0 %, 7.5 %, 10.0 %, wt/wt) into a classical white bread recipe to some physico-chemical, textural, nutritional, microbiological properties and also to sensory quality of fresh bread is compared. The results show that the addition of ESM, promoted as a natural additive for calcium fortified breads, generates a product with potential high acceptability degree for the consumers that need to improve the calcium daily intake.